2008
DOI: 10.1186/1471-2164-9-269
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pou5f1, Sox2, and Nanog downstream target genes with statistical confidence by applying a novel algorithm to time course microarray and genome-wide chromatin immunoprecipitation data

Abstract: Background: Target genes of a transcription factor (TF) Pou5f1 (Oct3/4 or Oct4), which is essential for pluripotency maintenance and self-renewal of embryonic stem (ES) cells, have previously been identified based on their response to Pou5f1 manipulation and occurrence of Chromatin-immunoprecipitation (ChIP)-binding sites in promoters. However, many responding genes with binding sites may not be direct targets because response may be mediated by other genes and ChIP-binding site may not be functional in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
172
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 54 publications
13
172
2
2
Order By: Relevance
“…In support of this view, chromatin immunoprecipitation-seq studies show that Sox2 can bind directly to the promoter of Dnmt3b [50,51], and a dramatic decrease of Zfp459 expression is observed after Sox2 knockout [52]. Our data also reveal that the methylation process begins immediately after Sox2 overexpression, while the induction of endogenous Nanog begins much later.…”
Section: Discussionsupporting
confidence: 78%
“…In support of this view, chromatin immunoprecipitation-seq studies show that Sox2 can bind directly to the promoter of Dnmt3b [50,51], and a dramatic decrease of Zfp459 expression is observed after Sox2 knockout [52]. Our data also reveal that the methylation process begins immediately after Sox2 overexpression, while the induction of endogenous Nanog begins much later.…”
Section: Discussionsupporting
confidence: 78%
“…To evaluate this hypothesis, we asked whether DEGs we identified are targets of POU5F1. We performed the comparative analysis of DEGs and Pou5f1 targets using BioGRID (BioGRID Version 3.4.139) (114) and published dataset (115). We identified 18 Pou5f1 target genes that are altered in ATZ lineage SG (Supplementary Figure S12B).…”
Section: Discussionmentioning
confidence: 99%
“…After removing all genes that were never expressed in our data, we tested the significance of the association between the Oct4 target genes and highly variable genes in 2-, 4-, and 8-cell embryos by Fisher's exact test (p values are, respectively, 0.005, 10 À9 and 4 3 10 À6 ). Analogously, we tested the enrichment of Sox2 target genes (Sharov et al, 2008) among the highly variable genes and found statistical significance at the 2-and 4-cell stages (p values 0.004 and 10 À5 ), but not at the 8-cell stage (p value 0.26). Finally, the enrichment test run on genes targeted by Oct4 and/or Sox2 gave the following p values for embryos at 2-, 4-, and 8-cell stage, respectively: 2 3 10 À4 , 3 3 10 À10 , and 3 3 10 À5 .…”
Section: Testing For Enrichment Of Oct4 and Sox2 Targets Among Highlymentioning
confidence: 99%
“…We downloaded a list of Oct4 target genes identified in three different publications (Loh et al, 2006;Matoba et al, 2006;Sharov et al, 2008) and selected only those that were targeted by Oct4 in at least two out of three publications. After removing all genes that were never expressed in our data, we tested the significance of the association between the Oct4 target genes and highly variable genes in 2-, 4-, and 8-cell embryos by Fisher's exact test (p values are, respectively, 0.005, 10 À9 and 4 3 10 À6 ).…”
Section: Testing For Enrichment Of Oct4 and Sox2 Targets Among Highlymentioning
confidence: 99%